2000
DOI: 10.1046/j.1365-2222.2000.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Selected recombinant Aspergillus fumigatus allergens bind specifically to IgE in ABPA

Abstract: The results demonstrate that Asp f 2, f 4, and f 6 can be used in the serodiagnosis of ABPA, while IgE antibody binding to Asp f 1 and f 3 was not specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
125
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 25 publications
5
125
0
7
Order By: Relevance
“…allergen.org). Most of the identified allergens elicit humoral immune responses [26][27][28][29], others are toxic to PBMC or are strongly homologous to human proteins, while some appear to prime primarily a Th2 T cell response [30][31][32][33]. Two allergens have been shown to stimulate both T and B cell responses from patients with ABPA, Asp f2 and Asp f16 [34,35].…”
Section: I I Introductionmentioning
confidence: 99%
“…allergen.org). Most of the identified allergens elicit humoral immune responses [26][27][28][29], others are toxic to PBMC or are strongly homologous to human proteins, while some appear to prime primarily a Th2 T cell response [30][31][32][33]. Two allergens have been shown to stimulate both T and B cell responses from patients with ABPA, Asp f2 and Asp f16 [34,35].…”
Section: I I Introductionmentioning
confidence: 99%
“…The involvement of Af-specific Th1 cytokines in allergic response raise the possibility of uncovering effective therapeutic modalities that would promote Th1 immune response and /or T-cell tolerance through regulatory T cells (CD4+ CD25+) in Af sensitized patients. In recent years, major Af allergens have been identified and purified using molecular cloning and expression protocol (3)(4)(5)(6). Asp f 3 has been recognized as a major allergen of Af, which elicited immediate wheal and flare skin reactions and strong IgE binding with a majority of ABPA patients' sera (1,4,7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that patients with ABPA react to a larger number of the recombinant allergens in this panel, some of which r Asp f2, f4 and f6 are considered specific to ABPA patients. [15][16][17][18] This technique therefore appeared to be very promising for ABPA diagnosis.…”
Section: Introductionmentioning
confidence: 99%